A importância do acolhimento na sala de espera de familiares de pacientes internados no CTI: uma revisão bibliográfica - ALVES, João Tiago Teixeira (2020)
The family member needs to be welcomed and comforted when his or her loved one is admitted to an Intensive Care Center, as a state of frailty arises, including distress and fear of losing a relative, as well as creating a new family routine with hospitalization and, With this, everyone needs to adapt to such a situation. Thus, a literature survey was conducted on the role of nurses in welcoming family members, emphasizing the importance of such act, as well as contributing to reflection on the theme in order to favor the interaction of the professional with the hospitalized patient's family member. This study is a bibliographic research developed through the Literature Review method that consists of a methodology that groups in a single study, the synthesis of works or theoretical references already existing in the literature that address a common theme of interest. thus allowing a broad analysis of the literature. In their articles, the authors sought to understand the comfort of patients 'families and to explain about strategies used by nurses to perform family members' welcoming, and also, how nurses act on those who have negative feelings. The welcoming of the family member in the waiting room of the Intensive Care Center is an extremely important subject, and needs to be addressed more by researchers in order to know more about the experiences in the intensive setting. It was identified ways to receive and accompany the family member before and during the hospitalization process, through communication and dialogue, enabling to establish affective bond between those involved. The nurse also has the role of keeping the relative informed about all the procedures. Numerous difficulties were encountered in the attempt to provide efficient reception, but it is considered too important to talk about the lack of interest of the health professional, who is often unwilling to offer a quality service, leaving something to be desired in the receptivity of the family member, often not providing information or is not enough for the necessary care.